RP-HPLC Method Development and Validation for Simultaneous Estimation of Benidipine Hydrochloride and Chlorthalidone in Pharmaceutical Dosage Form - Shaikhmulani, Hasan; Tamboli, Ashpak M; Tamboli, Naziya A; Kshirsagar, Rohan T (Indian Journal of Pharmacy & Drug Studies, 2023)
A simple, precise, rapid and accurate reverse phase High Performance Liquid Chromatography (HPLC) method was developed for the estimation of Benidipine Hydrochloride and Chlorthalidone in bulk and tablet dosage form. C18 C-18 Agilent Zorbax Bonus – RP (250 x 4.6 mm, Particle size -5 Micron) was used in this method. The mobile phase comprises of Methanol and 0.1% Orthophosphoric acid (45:55v/v) with flow rate 1 mL/min (Photodiode array Detector). The retention time for Benidipine Hydrochloride was 1.09 min and for Chlorthalidone was 3.52 min. The detection concentration was linear over 32-48 μg/mL for Benidipine Hydrochloride and 100-150 μg/mL for Chlorthalidone. The regression equation of Benidipine Hydrochloride and Chlorthalidone were found to be y = 50184x-30070 and y = 37102x-74642 respectively with regression coefficient of Benidipine Hydrochloride and Chlorthalidone were 0.999 and 0.999. So, the present work is aimed for development of simple, reproducible chromatographic RP-HPLC method for simultaneous estimation of Benidipine Hydrochloride and Chlorthalidone. The developed method was successfully validated in accordance to ICH guideline. Hence the method can be conveniently adopted for routine analysis in quality control laboratories.